Hubungan Antara Tingkat Pengetahuan Tentang PHBS Keluarga Dengan Perilaku BAB Di Sungai Di Dusun Bedog Desa Mlaten Kecamatan Puri Kabupaten Mojokerto - Dwi w, Binarti (JURNAL KEPERAWATAN SEHAT, 2015)
ABSTRACTOne of the 10 indicator of PHBS is healthy latrine use. The observation conducted by research at village Bedog Mlaten district Puri Mojokerto, found people who use the river as a means of defecating. The purpose of this study was to determine the relationship between the level of knowledge at family PHBS (Clean and Healthy Behaviors), behavior in the river in the village Bedog Mlaten district Puri Mojokerto. The research design used in this study is analytic correlation with cross sectional approach. The population in the study were all families (households) in the Village Bedog Mlaten District Puri Mojokerto as many as 248 families. The sampling technique used is simple random sampling. The number of samples in this study were 153 respondents. The research instrument used was a questionaire. To determine the relationship between variables used Spearmans Rho correlation test (α = 0.05). From the results, most respondents to defecate in the river as many as 97 respondents (63.4%), there is a relation ship between the level of knowledge of PHBS chapter families with behavior in the river in the Village Bedog Mlaten District Puri Mojokerto with a significance value of 0.000 and a correlation value of 0.810. People who have the knowledge of PHBS, indirectly would be motivated to implement the program in a family environment. Knowledge of PHBS are owned by the public will affect the behavior of BAB in river addition to other factors that also may affect the behavior of BAB in river.Keywords : Knowledge level, PHBS, Behavior